Rancang Bangun Baterai Alternatif Menggunakan Metode Sel Volta dengan Charger Panel Surya - Agnes Angela Turnip, Yenny; Mungkin, Moranain; Maizana, Dina; Satria, Habib (ELECTRON Jurnal Ilmiah Teknik Elektro, 2024)
Currently, many renewable energies are utilized by the world for electrical energy sources. In the future, renewable energy will be a new breakthrough for researchers to develop a technology whose energy source comes from nature and can be continuously renewed without limits. One of the developments in this technology is the development of alternative batteries in salt water (NaCl) solutions. NaCl is a type of electrolyte solution whose solution properties are able to conduct electric current. In electrolyte solutions, electrodes play an important role as a medium for conducting electricity (conductors) in batteries. This battery is designed using copper (Cu) electrodes as the cathode and zinc (Zn) as the anode with the voltaic cell method. The purpose of this study is to replace the H2SO4 solution with a more environmentally friendly salt water electrolyte solution. Based on the test results, the alternative battery produces an electric voltage of 4.17 Volts at a concentration of 3 M using 6 electrode cells arranged in series and applied to solar panels